Evaluasi Strategi Bisnis Balanced Scorecard Pada PT. Raja Indonesia Perkasa - Maziyyah Richa Adnina; Megafatin Qomariyah Subagyo; Bakhrul Huda (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
PT Raja Indonesia Perkasa is engaged in the manufacturing industry in the textile sector by producing equipment and wholesale trade in household appliances and furniture trying to evaluate the company's performance. The purpose of this study was to determine the evaluation of the strategy according to the vision and mission applied to PT Raja Indonesia Perkasa using the balanced scorecard concept. Strategy evaluation in the company is useful for assessing the performance of a company, knowing the company's position in an effort to achieve its goals. The increasingly fierce competition in the 21st century and the economic turmoil during the global pandemic due to Covid-19 require PT Raja Indonesia Perkasa as a company that also carries out exports and imports to stay afloat. Descriptive quantitative research methodology with two sources of primary and secondary data. Data processing method using Balanced Scorecard analysis. The researcher chose this method because, from a subjective point of view, the researcher saw the success of the business run by the company PT Raja Indonesia Perkasa which is getting more and more enthusiasts or consumers in the midst of fierce competition in the business world that is happening today. The results of this study indicate that the indicators for measuring the performance of the financial perspective are the best with a score of 145,06%, followed by the customer perspective on average 55% said to be good, the business perspective on average 31.19% said to be good, growth and learning an average of 2.4% is said to be less good.